PELAKSANAAN SHORT MESAGGE SERVICE (SMS) REMINDER DI RUMAH SAKIT SYAFIRA PEKANBARU - Tri Purnama Sari; Uci Gumarsih (Sistem Informasi, 2016)
SMS Reminder is a Short Message Service that broadcast in one direction, which means that incoming SMS will not be replied by system, and serves to remind the user. The system will automatically send SMS to multiple phone numbers which have been entered in database previously. The delivery time of SMS must be in accordance with a predetermined scheduling. The purpose of this study is to get an overview of implementation on SMS Reminder activities at Syafira Hospital Pekanbaru. The method use in this research is descriptive qualitative approach. The numbers of informants were two people that officer and person in charge SMS Reminder section. These results indicate that the Human Resources of SMS Reminder amounted to two person have educational backgrounds S1 and have been not trained specifically on SMS Reminder and the service of SMS Reminder have not Standard Operating Procedures (SOPs), as well as the lack of a telephone to perform SMS Reminder. Suggestions on this research is SMS Reminder officers should be trained in communication and procedures for the implementation of SMS Reminder and make Standard Operating Procedures (SOPs) so that the officer has a reference in carrying out their duties.